Engineering monoclonal antibody-based contraception and multipurpose prevention technologies. Issue 2 (8th June 2020) - Anderson, Deborah J; Politch, Joseph A; Cone, Richard A; Zeitlin, Larry; Lai, Samuel K; Santangelo, Philip J; Moench, Thomas R; Whaley, Kevin J
Abstract: Sexually transmitted infections are highly prevalent, and over 40% of pregnancies are unplanned. We are producing new antibody-based multipurpose prevention technology products to address these problems and fill an unmet need in female reproductive health. We used a Nicotiana platform to manufacture monoclonal antibodies against two prevalent sexually transmitted pathogens, HIV-1 and HSV-2, and incorporated them into a vaginal film (MB66) for preclinical and Phase 1 clinical testing. These tests are now complete and indicate that MB66 is effective and safe in women. We are now developing an antisperm monoclonal antibody to add contraceptive efficacy to this product. The antisperm antibody, H6-3C4, originally isolated by Shinzo Isojima from the blood of an infertile woman, recognizes a carbohydrate epitope on CD52g, a glycosylphosphatidylinositol-anchored glycoprotein found in abundance on the surface of human sperm. We engineered the antibody for production in Nicotiana ; the new antibody which we call "human contraception antibody, " effectively agglutinates sperm at concentrations >10 μg/ml and maintains activity under a variety of physiological conditions. We are currently seeking regulatory approval for a Phase 1 clinical trial, which will include safety and "proof of principle" efficacy endpoints. Concurrently, we are working with new antibody production platforms to bring the costs down, innovative antibody designs that may produce more effective second-generation antibodies, and delivery systems to provide extended protection. Abstract : We are engineering monoclonal antibodies and delivery systems for multipurpose prevention technology products that will concurrently prevent sexually transmitted infections and unplanned pregnancies, addressing an important unmet need in reproductive health.